Proteomic Approach to Study the Effect of Pneumocystis jirovecii Colonization in Idiopathic Pulmonary Fibrosis - Jonás Carmona-Pírez; Rocío Salsoso; Eléna Charpentier; Cinta Olmedo; Francisco J. Medrano; Lucas Román; Carmen de la Horra; Yaxsier de Armas; Enrique J. Calderón; Vicente Friaza (Journal of Fungi, 2025)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and interstitial disease with an unclear cause, believed to involve genetic, environmental, and molecular factors. Recent research suggested that Pneumocystis jirovecii (PJ) could contribute to disease exacerbations and severity. This article explores how PJ colonization might influence the pathogenesis of IPF. We performed a proteomic analysis to study the profile of control and IPF patients, with/without PJ. We recruited nine participants from the Virgen del Rocio University Hospital (Seville, Spain). iTRAQ and bioinformatics analyses were performed to identify differentially expressed proteins (DEPs), including a functional analysis of DEPs and of the protein–protein interaction networks built using the STRING database. We identified a total of 92 DEPs highlighting the protein vimentin when comparing groups. Functional differences were observed, with the glycolysis pathway highlighted in PJ-colonized IPF patients; as well as the pentose phosphate pathway and miR-133A in non-colonized IPF patients. We found 11 protein complexes, notably the JAK-STAT signaling complex in non-colonized IPF patients. To our knowledge, this is the first study that analyzed PJ colonization’s effect on IPF patients. However, further research is needed, especially on the complex interactions with the AKT/GSK-3β/snail pathway that could explain some of our results.